2002
DOI: 10.1080/000163502753472014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of short-root anomaly in healthy young adults

Abstract: Short-root anomaly (SRA), occurring mostly in maxillary incisors, is defined as developmentally very short, blunt dental roots. The condition has a genetic background and is related to hypodontia. Earlier population studies have been based on schoolchildren with developing dentitions and have indicated prevalence figures between 1% and 10%. We studied a random sample of existing panoramic radiographs of 2000 university students for SRA. Roots as long as or shorter than the crowns in the incisors and visually e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 22 publications
4
51
2
Order By: Relevance
“…27 The prevalence of SRA in the Finnish population is 1.3%. 41 In our study the defect categories D2 and D3 fulfill the criteria of short root anomaly. In the TBI group 10/10, and in the non-TBI group 1/5 patients had alterations of this magnitude in relative root length, giving a prevalence of 73.3%.…”
Section: Discussionmentioning
confidence: 99%
“…27 The prevalence of SRA in the Finnish population is 1.3%. 41 In our study the defect categories D2 and D3 fulfill the criteria of short root anomaly. In the TBI group 10/10, and in the non-TBI group 1/5 patients had alterations of this magnitude in relative root length, giving a prevalence of 73.3%.…”
Section: Discussionmentioning
confidence: 99%
“…This racial variation, together with a strong familial background, indicates that this anomaly has a strong genetic influence (16). Apajalhti et al (19) found a prevalence of 1.3% among healthy young adults. The male:female ratio is reported to be 1:3 (19).…”
Section: Discussionmentioning
confidence: 99%
“…Apajalhti et al (19) found a prevalence of 1.3% among healthy young adults. The male:female ratio is reported to be 1:3 (19). Presence of generalized short roots was found in combination with systemic conditions such as hypoparathyrodism, Stevens-Johnson syndrome, Rothmund-Thomson syndrome, exposure to irradiation and thalassaemia disorders (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…The condition designated as short root anomaly or SR anomaly (Lind, 1972) occurs mostly in maxillary central incisors (Apajalahti et al, 2002) and is described in modern clinical literature (de Man, 1979;Apajalahti et al, 2002;Roinioti and Stefanopoulos, 2007). According to Turp and Alt (1998), variations in the root size and form of permanent teeth are determined by separate hereditary factors; however, tooth germ distortion or injury by trauma is also a possible origin of short roots (Hillson, 2005).…”
Section: Discussionmentioning
confidence: 99%